2021
DOI: 10.3390/su13179693
|View full text |Cite
|
Sign up to set email alerts
|

An Introductory Energy Course to Promote Broad Energy Education for Undergraduate Engineering Students

Abstract: Engineering graduates must be prepared to support our world’s need for a clean and sustainable energy future. Complex problems related to energy and sustainability require engineers to consider the broad spectrum of interrelated consequences including human and environmental health, sociopolitical, and economic factors. Teaching engineering students about energy within a societal context, simultaneous with developing technical knowledge and skills, will better prepare them to solve real-world problems. Yet few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Our results also suggest that sociotechnical classes are effective in developing all students' understanding of sociotechnical engineering. Similar results have been determined from studies conducted with first-year students enrolled in introduction to engineering sociotechnical classes [10,36] and students enrolled in energy-focused sociotechnical classes [11,19]. However, Leydens et al [18] found that students' views of social justice and engineering did not change as a result of being enrolled in engineering science classes where social justice was integrated into the coursework.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our results also suggest that sociotechnical classes are effective in developing all students' understanding of sociotechnical engineering. Similar results have been determined from studies conducted with first-year students enrolled in introduction to engineering sociotechnical classes [10,36] and students enrolled in energy-focused sociotechnical classes [11,19]. However, Leydens et al [18] found that students' views of social justice and engineering did not change as a result of being enrolled in engineering science classes where social justice was integrated into the coursework.…”
Section: Discussionsupporting
confidence: 66%
“…For example, using contextualized engineering problems in homework problem sets or in class that expose students to the social or human side of engineering can add context to engineering science classes [40]. Real-world, contextualized applications of engineering that require students to think about engineering as sociotechnical can also be implemented in these engineering courses as described by Hoople et al [11], DeWaters et al [19], and Leydens et al [18].…”
Section: Looking Forward and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation